(3JaSjQ GdKYGdHis - (3YHO GdQMef Hf eMeO Hf eNdha GdKYGdHj GdLRGFQj, CHh RjO,J (B875 (3g` s ((3eMeO Hf eMeO Hf YHO Gddg GdOfOGfi s)
(3ChdgG (B:s
(3ShQI Gdcga hgPg GdShQI ecjI ai bhd LejY GdeaSQjf hQhi Cf GdfHi Udi Gddg Ydjg hSde bGd (B:(3CdG CNHQce HShQI YXegG eG Hjf GdSehGJ hGdGQV def LGA HgG ef GdGLQ s
(3BNQgG (B:s
(3hQhi Yf GdfHi Udi Gddg Ydjg hSde Efg bGd (B: (3EPG SdeJe Ydi aSdehG Ydi GdeQSdje aEfeG CfG CMOge Udi Gddg Ydjg hSde hYdi Edg hYdi LejY GdfHjjf ced Chd GdLRA GdKGfi ef JCdja GdTjN GdKYGdHi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B192s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs